Analisis Dampak Sertifikasi Produk Halal Terhadap Kegiatan Ekonomi dan Sosial - Putra, Ifaldy Airomy; Ambariyanto, Ambariyanto (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to determine the impact of halal certification on economic and social activities. By using comparative theory comparing the situation before and after the product is halal certified. This study uses the McNemar analysis test approach to determine the impact of halal certification on the economic and social activities of MSME producers. Primary data was collected through distributing questionnaires with a sample of 56 MSME producers with halal certification in Sumenep Regency, sampling using simple random sampling techniques. The findings of this study: the impact of halal certification in the economic perspective of producers has changed, in sales there has been an increase after being halal certified, this is because producers can give confidence to consumers. Then there is an increase in the producer's market share, with halal certification producers are free to market their products because they do not violate the law of halal certification obligations Law 33 of 2014 concerning halal product guarantees (JPH). Meanwhile, in producer profits, there has been a decrease, this is because producers cannot increase selling prices, but must maintain and even improve product quality if possible. In producer capital, there is a decrease, because in halal certification there is no additional producer capital, and finally in the form of a decrease in demand for producer products, this condition is due to consumers also paying attention to prices, flavors and services from producers, so that, even though halal certification does not guarantee that product demand will increase. Then in the social perspective of producers in the form of increased public trust, increased public trust because with halal certified products producers feel that consumers have no doubts about the raw materials and hygiene of the producers. Whereas in the alms of producers there has been a decrease, this is because the attitude of alms producers does not depend on the existence of legality or halal certification, but depends on the awareness and religious level of the producers. Meanwhile, in the halal lifestyle of producers there is no change both before and after being halal certified.